The Role of Organizational Commitment in Mediating the Influence of Workload, Work Environment, and Organizational Support on Performance Wakatobi Regency Hospital Employee - Karsinah Sidi; Andi Jam'an; Ismail Rasulong (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of workload, work environment, and organizational support on employee performance at Wakatobi Regency Hospital with organizational commitment as a mediating variable. This study uses a quantitative approach by distributing questionnaires to 188 employees at the Wakatobi Regency Hospital. Data analysis used the Structural Equation Modeling method based on Partial Lrast Square (PLS-SEM) through the SmartPLS application to test the direct and indirect influence between variables. The results of the study show that workload does not have a significant effect on employee performance, but it has a significant effect on organizational commitment. The work environment has a significant effect on employee performance, but it does not have a significant effect on organizational commitment. Organizational support does not have a significant effect on employee performance, but it has a significant effect on organizational commitment. Furthermore, organizational commitment has been proven to have a significant effect on employee performance. The results of the mediation test showed that organizational commitment was able to mediate the influence of workload and organizational support on employee performance, but did not mediate the influence of the work environment on employee performance. The findings of this study confirm that organizational commitment has an important role in improving employee performance. Therefore, the management of the Wakatobi Regency Hospital needs to pay attention to the management of the workload proportionally and increase organizational support to strengthen employee commitment so that it can encourage optimal performance improvement.